Virtual screening, synthesis and biological evaluation of DNA intercalating antiviral agents. Issue 16 (15th August 2017) - Klimenko, Kyrylo; Lyakhov, Sergey; Shibinskaya, Marina; Karpenko, Alexander; Marcou, Gilles; Horvath, Dragos; Zenkova, Marina; Goncharova, Elena; Amirkhanov, Rinat; Krysko, Andrei; Andronati, Sergei; Levandovskiy, Igor; et al.
Graphical abstract: Highlights: Virtual screening to discover potential nucleic acids intercalators. Two hits active against Vaccinia virus were found. Intercalating mechanism was proposed for the hits. Abstract: This paper describes computer-aided design of new anti-viral agents against Vaccinia virus ( VACV ) potentially acting as nucleic acid intercalators. Earlier obtained experimental data for DNA intercalation affinities and activities against Vesicular stomatitis virus ( VSV ) have been used to build, respectively, pharmacophore and QSAR models. These models were used for virtual screening of a database of 245 molecules generated around typical scaffolds of known DNA intercalators. This resulted in 12 hits which then were synthesized and tested for antiviral activity against VaV together with 43 compounds earlier studied against VSV . Two compounds displaying high antiviral activity against VaV and low cytotoxicity were selected for further antiviral activity investigations.